Analisis Pengetahuan Mahasiswa Universitas Jember Terkait Mitigasi Bencana Gempa Bumi - Salfa Zahroh Ahadah; Hildatul Zannah; Rohmi Khoirun N; Rif’ati Dina Handayani; Sri Astutik (Jurnal Ilmiah Wahana Pendidikan, 2023)
Jember is a disaster-prone area, especially earthquakes. Disasters can cause many losses, ranging from casualties to property so that knowledge about disaster mitigation is very important to minimize the consequences caused. The purpose of this study is to determine the level of knowledge of Jember University students related to earthquake disaster mitigation. The research method used in this study is descriptive quantitative. This research was conducted on students of the University of Jember using test questions consisting of 10 questions. Data analysis was conducted by giving a score range of 1-4 on each question item, then the total score was converted into a score range of 0-100. The results of the analysis showed that the average overall score was 69.4, which is equivalent to a percentage of 69.4%. Therefore, the level of knowledge of Jember University students related to disaster mitigation is in the moderate category.